(untitled) (Maritime Park: Journal of Maritime Technology and Society, 2023)
This research aims to analyze the economic and environmental feasibility of using biodiesel as an alternative fuel for fishing vessels in Indonesia. This research uses cost-benefit analysis, greenhouse gas emission analysis, and sensitivity analysis methods to evaluate the impact of biodiesel use on economic and environmental aspects. The results show that the use of biodiesel as an alternative fuel for fishing vessels in Indonesia is economically feasible, as it can save fuel costs, reduce dependence on imported diesel, and increase the added value of fishery products. The use of biodiesel is also environmentally feasible, as it can reduce energy consumption, greenhouse gas emissions, and other pollutant emissions generated by fishing vessels. The economic and environmental feasibility of using biodiesel as an alternative fuel for fishing vessels in Indonesia is quite stable and not sensitive to changes in conditions that may occur in the future. This research provides recommendations for the government, fishery industry, and society to support the development and implementation of biodiesel as an environmentally friendly alternative fuel for fishing vessels in Indonesia.